A reliability model for a wafer FAB. Issue 1 (1st January 2017) - Jang, Joong S.; Park, Sang C.
Abstract: Proposed in this paper is a new reliability model for a wafer fabrication plant (FAB). The reliability prediction of a FAB is essential for various activities; feasibility evaluation, comparing competing designs, identifying potential reliability problems, planning maintenance and logistic support strategies, and input to other studies such as life-cycle cost analysis or order selection. The conventional reliability model, however, is not appropriate for a FAB because of inherent attributes of the manufacturing system; concurrent production of various products, reentrant material flows, and the recipe arrangement problem. To overcome this problem, this paper proposes a new reliability model of a FAB consisting of three reliability functions; reliability function of an entire FAB, reliability functions of tool groups, and reliability functions of FAB tools. To demonstrate the proposed reliability model, a simulation model is constructed based on a wafer FAB data-set. The simulation experiments are carried out with commercial software MOZART®.